Deployment of a Smart Handwashing Station in a School Setting During the COVID-19 Pandemic: Field Study - Herbert, Jeremy; Horsham, Caitlin; Ford, Helen; Wall, Alexander; Hacker, Elke (JMIR Publications, 2020)
BackgroundHand hygiene is one of the most effective ways to remove germs, prevent the spread of infectious pathogens, and avoid getting sick. Since the COVID-19 pandemic began, health authorities have been advocating good hand hygiene practices. ObjectiveThe primary aim of this study is to field test a prototype smart handwashing station deployed in a school setting during the COVID-19 pandemic. MethodsWe deployed a smart handwashing station and examined key technological considerations including connectivity, security, and data management systems, as well as the health and safety of users. ResultsThe smart handwashing station was deployed for 10 days in a school setting in Australia during the COVID-19 pandemic. The smart handwashing station's electrical components remained operational during field testing and underwent robust cleaning protocols each day. The handwashing station was used 1138 times during the field test and there was no COVID-19 transmission at the school during the testing. ConclusionsThis study demonstrates that a personalized feedback approach using technology can successfully be implemented at a school and can provide a platform to improve hand hygiene among school-aged children.